2013
DOI: 10.1007/s00467-012-2396-1
|View full text |Cite
|
Sign up to set email alerts
|

Policy variation in donor and recipient status in 11 pediatric renal transplantation centers

Abstract: Management policies for renal Tx in children vary considerably between centers and nations. This has a direct impact on the delivered care, and by extrapolation, on health outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Firstly, our study cohort was small and it was analyzed retrospectively. However, we believe it is representative for a Belgian tertiary center, where an opting-out system for deceased donors has been adopted and as previously showed in a comparative analysis between the Netherlands and Belgium by van Huis et al 4 Furthermore, patients were transplanted over the span of 20 years. In that time, the center policies and the attitude of the medical team toward living donation have evolved, so possibly a number of families who were not offered the possibility of living donation 20 years ago would have gotten it in the recent years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, our study cohort was small and it was analyzed retrospectively. However, we believe it is representative for a Belgian tertiary center, where an opting-out system for deceased donors has been adopted and as previously showed in a comparative analysis between the Netherlands and Belgium by van Huis et al 4 Furthermore, patients were transplanted over the span of 20 years. In that time, the center policies and the attitude of the medical team toward living donation have evolved, so possibly a number of families who were not offered the possibility of living donation 20 years ago would have gotten it in the recent years.…”
Section: Discussionmentioning
confidence: 99%
“…3 The differences in approach toward LD KT between the Netherlands and Belgium also exist in pediatric centers and are mirrored in the difference between the incidence of living donation in pediatric kidney recipients: 48% vs 26%, respectively. 4 The argument often used in Belgian centers in favor of DD KT is that pediatric recipients will likely require more than one transplant during their life and parents' kidneys are saved for later. 4 As of 2015, there is an increase in the number of the In this study, we retrospectively reviewed the choice of donor source (deceased vs. living) in all children who underwent KT at the Ghent University Hospital between 1996 and 2016.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is a registry study, with limited set of variables, so several kidney transplantation-related factors that may have contributed to a country's ability to transplant pediatric patients are unavailable. Previous studies showed that differences in kidney transplantation policies, such as recommendations regarding living or deceased donation, the maximum accepted donor age, cold ischemia time, minimum accepted recipient age, and HLA-matching, may also play a role in explaining country differences in access to transplantation, 4,11 along with various cultural, local, and logistic factors. 17 All these factors may partly explain the variation in access to kidney transplantation, and their absence in our analyses may have led to some degree of residual confounding.…”
Section: Other Potential Determinants Of Access To Kidney Transplantationmentioning
confidence: 99%
“…9 Considering the diversity of kidney transplantation policies and practices across Europe, access to pediatric kidney transplantation and graft failure rates are likely to vary between countries. 4,10,11 Although international differences in kidney transplantation-and graft failure rates have been described in the adult kidney transplant population in high-income countries, 12 the existence of any country-level differences remains largely unknown in the pediatric population. In this study, we aim to determine the extent of country variation in kidney transplantation-and graft failure rates, and to assess the impact of both patient-and country-level determinants in explaining this variation.…”
Section: Introductionmentioning
confidence: 99%